2017
DOI: 10.1039/c7me00024c
|View full text |Cite
|
Sign up to set email alerts
|

Studying physisorption processes and molecular friction of cycloparaphenylene molecules on graphene nano-sized flakes: role of π⋯π and CH⋯π interactions

Abstract: We theoretically study, by means of dispersion-corrected and cost-effective methods, the strength of non-covalent interactions between cyclic organic nanorings and nano-sized graphene flakes acting as substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…For the study of [8]CPP and its self-aggregation process on graphitic surfaces employing atomistic simulations, we first developed a force field able to reproduce the involved nonbonded intermolecular interactions, motivated by previous studies [20] of the energy profile of [8]CPP interacting with finite-size graphene surfaces (circumcoronenes and circumcircumcoronenes). Linear para-phenylenes were formerly studied by Olivier et al [53] employing the AMBER-OPLS force field, [54] with scaled parameters for the nonbonded interactions and refitted torsional energy profiles to reproduce p-quinquephenyl phase behavior.…”
Section: Force Field Parameterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…For the study of [8]CPP and its self-aggregation process on graphitic surfaces employing atomistic simulations, we first developed a force field able to reproduce the involved nonbonded intermolecular interactions, motivated by previous studies [20] of the energy profile of [8]CPP interacting with finite-size graphene surfaces (circumcoronenes and circumcircumcoronenes). Linear para-phenylenes were formerly studied by Olivier et al [53] employing the AMBER-OPLS force field, [54] with scaled parameters for the nonbonded interactions and refitted torsional energy profiles to reproduce p-quinquephenyl phase behavior.…”
Section: Force Field Parameterizationmentioning
confidence: 99%
“…The first solid-state characterization of [6]CPP revealed a tubular-like structure, [14] but a recent study revealed that the crystallographic structure might depend on the crystallization conditions, also finding a herringbone configuration a few kcal mol −1 more stable than the tubular one. [20] In the present study, we wish to go a step further and employ a tailored force field and molecular dynamics (MD) simulations to predict the supramolecular structure of thin films of CPPs on graphite surfaces. In these conditions, no solvent molecules are occluded inside the [6]CPP cavity, and thus, a concave-convex structure appears (i.e., molecules tightly packed in a T-like shape minimizing the internal space inside the cavities).…”
mentioning
confidence: 99%
See 3 more Smart Citations